Analysis of Determinant Purchase Decisions Halal Cosmetic By Generation Z on Tiktok - Haliza Vita Humahira; Ekawaty, Marlina (Islamic Economics and finance in Focus, 2026)
The rapid development of the halal pharmaceutical and cosmetics industry has ranked second in the SGIE 2024/2025 report. This means that consumer demand for halal cosmetics and personal care is increasing. This study aims to analyze the influence of e-WOM, halal awareness, understanding of Islamic consumption, and price perception on purchasing decisions for Glad2Glow halal cosmetics on TikTok. Several studies have highlighted the relationship between e-WOM, halal awareness, and price perception in halal cosmetic purchasing decisions, but there are still few studies that integrate understanding of Islamic consumption as an important variable, especially in purchasing decisions for Glad2Glow halal cosmetics on the TikTok platform. The research method chosen is binary logistic regression analysis with primary data through an online questionnaire for Gen Z Muslim consumers. The results of the study state that the variables e-WOM, halal awareness, understanding of Islamic consumption, and price perception partially influence purchasing decisions for Glad2Glow halal cosmetics on TikTok. This research is expected to be useful for the halal cosmetic industry in designing and developing effective products and marketing strategies to reach Gen Z through social media.